Linguistic Diversity and Disparity in the Periphery - Tankosić, Ana (Curtin University, 2023)
This thesis uses methods of linguistic ethnography to explore linguistic diversity and disparity in the global periphery. In terms of diversity, it investigates how language users nurture their translingual identities by engaging in creative translingual practices, and relocalising everyday communicative resources. In terms of disparity, it examines the challenges of Culturally and Linguistically Diverse migrant communities in Australia in cases when their translingual identity becomes grounds for ling